Toxic effects of polystyrene nanoplastics on MDA-MB-231 breast cancer and HFF-2 normal fibroblast cells: viability, cell death, cell cycle and antioxidant enzyme activity - Hanie Sadeghinia; Parichehr Hanachi; Reihaneh Ramezani; Samaneh karbalaei (Environmental Sciences Europe)
Abstract Background Environmental nanoplastics pose a potential health risk due to human exposure, necessitating studies on their cellular effects. This study aims to assess the toxic and antibacterial properties of polystyrene nanoplastics (PS-NH2) on MDA-MB-231 breast cancer cells and HFF-2 fibroblast cells, while also evaluating their oxidative stress responses. Additionally, the study explores the anti-tumor effects and apoptosis induction by PS-NH2. The primary objectives were to determine the cytotoxicity, antibacterial efficacy, and oxidative stress response of PS-NH2 at different concentrations and sizes. The study also aimed to investigate the mechanism of cell death, including apoptosis, necrosis, cell cycle arrest, and changes in antioxidant enzyme activity (SOD and GPx). Methods Nanoplastic properties were characterized using FTIR, FESEM, and zeta potential analysis. Antibacterial effects were assessed using the agar dilution method, while the MTT assay determined cytotoxicity in MDA-MB-231 and HFF-2 cells. Apoptosis, necrosis, cell cycle arrest, and antioxidant enzyme activities (SOD, GPx) were also evaluated. Results FTIR analysis confirmed the amino-functionalization of PS-NH2 with a wide peak at 3386 cm-1, and zeta potential indicated a neutral charge. PS-NH2 showed no antibacterial activity against E. coli or Staphylococcus aureus at sizes of 90, 200, and 300 nm. Cytotoxicity assays revealed dose-dependent decreases in cell viability for both cell lines. SOD and GPx activity decreased significantly with increasing PS-NH2 concentrations. Both cell lines underwent apoptosis, with cell accumulation in the G1 and sub-G1 phases, indicating apoptotic cell death. Conclusions PS-NH2 exhibits dose- and size-dependent cytotoxicity in MDA-MB-231 and HFF-2 cells. Smaller particle sizes and higher concentrations of PS-NH2 enhance oxidative stress, leading to apoptosis and cell cycle arrest. Graphical Abstract